MANDA İDARESİNDEN GÜNÜMÜZE ÜRDÜN VE TÜRKİYE İLİŞKİLERİ - ÇEVİK, AHMET CAN (Fırat Üniveristesi, 2008)
Resmi adı ile Haşimi Ürdün Krallığı, Kuzeyde Suriye, Kuzeydoğu da Irak, güneydoğu ve güneyde Suudi Arabistan, batıda İsrail ile çevrili bir Ortadoğu ülkesidir. Tarih boyunca çeşitli devletlerin egemenlikleri altına giren ve çeşitli uygarlıkların etkilediği Ürdün toprakları,1516'da Osmanlı imparatorluğunun Memlukları yenilgiye uğratmasıyla yaklaşık dört yüzyıl Türk egemenliği altında kalmış, Birinci Dünya Savaşı sonrasında ise bölge İngiliz mandasına bırakılmıştır.Bağımsızlık sonrasında Ürdün konumu nedeniyle Filistin sorunundan en fazla zarar gören ülkelerden biri olmuştur. İsrail'in kuruluşunun ardından 1948 Savaşında diğer Arap ülkeleriyle beraber savaşa katılan Ürdün, bu tarihten sonra savaştan kaçan mültecilere kapılarını açmış, bu durum iç savaşın ortaya çıkışında temel faktörlerden birisi olmuştur. Temmuz 1951'de Kudüs'de Mescid-i Aksa çıkışında Filistinli bir milliyetçi tarafından suikast sonucu öldürülen Kral Abdullah'ın ardından önce oğlu Tallal Kral olmuş, bir yıl sonra da Krallık, 1999 yılında kadar ülkeyi idare edecek olan Kral Hüseyin'e verilmiştir.Ürdün iç ve dış politikalarında, kendi yönetiminin hedeflediği noktaya ulaşmak için çalışmayı ve bu doğrultuda çıkarlarını korumayı amaç edinmiştir.Türkiye Ürdün'ü güvenilir bir müttefik olarak görmektedir. Dönem içerisinde ilişkiler çok farklı boyutlarda kazanarak gelişmiştir. Daha da ileri götürülmesinin her iki ülkenin lehine olacağı değerlendirilmektedir. Ürdün İsrail ile imzalamış olduğu barış antlaşması sayesinde ve kendi iç dinamikleri açısından sorunsuz bir yapı arz etmesi nedeniyle bölgede gittikçe artan bir öneme sahiptir. Türkiye'nin Orta doğudaki siyasi ve ekonomik çıkarlarının korunması açısından Ürdün ve Türkiye ilişkilerinin öncelikle korunması ve zamanla daha da geliştirilmesi her iki ülkeye olduğu kadar bölgeye de büyük faydalar sağlayacağı düşünülmektedir.

Jordan; Middle East Country, officially Hashemite Kingdom of Jordan, bordered by Israel (W), Syria (N), Iraq (NE), and Saudi Arabia (E, S). The region of present-day Jordan was conquered successively by the Seleucids (4th cent. BC), Romans (mid-1st cent. AD), and Muslim Arabs (7th. cent.). After the Crusaders captured (1099) Jerusalem, it became part of the Latin Kingdom of Jerusalem. The Ottoman Turks gained control in 1516, and what is now Jordan remained in the Ottoman Empire until World War I. In 1920 Transjordan (as it was then known) was made part of the British mandate of Palestine.The country gained independence in 1946, and the name was changed (1949) to Jordan, reflecting its acquisition of land of the Jordan.Abdullah ibn Husain, a member of the Hashemite dynasty that headed Jordan since 1921, was assassinated in 1951. His grandson, Hussein I, became king the following year. Jordanian forces were routed by Israel in the 1967 war and Jordan lost the West Bank. Jordan renounced (1974; reaffirmed 1988) its claims to the West Bank in order to allow the Palestine Liberation Organization eventually to organize a state in this territoryGrowing hostility between Hussein and Palestinian guerrilla organizations operating in Jordan led to a brief civil war in 1970, and guerrilla bases were destroyed in 1971. Jordan also joined most of the other Arab countries in opposing the 1979 peace treaty between Egypt and Israel. It was officially neutral in the Persian Gulf War, but many Jordanians supported Iraq. In 1991 Jordan began peace talks with Israel, and a treaty was signed in 1994.Hussein continued to promote peace between Arabs and Israelis until his death in 1999; he was succeeded by his son Abdullah II who pledged to work toward a more open government and to ease restrictions on public expression. Although there has been some progress in terms of economic development, the country remains dependent on tourism, which has been hurt by its location between Israel and Iraq. Political liberalization has been slow in coming.Turkey considers Jordan as a friendly ally. The relations between two countries improved and gained accelaration in different aspects. Improving the relations will be beneficial for both countries.Also in the aspect of Turkeys? economic and politicial interests in the Middle East, improvement of the relations between two countries will be beneficial for both countries as well as the region.
From mandatory management to at the present Urdun and Turkey relations
Keywords: Tarih